2009
DOI: 10.1179/cim.2009.10.4.218
|View full text |Cite
|
Sign up to set email alerts
|

The transmeatal approach: a new technique in cochlear and middle ear implants

Abstract: The transmeatal approach (TMA) is a new approach for cochlear and middle-ear implantation. It is an open-tunnel technique that differs from closed transcanal non-mastoidectomy approaches. The TMA involves creating an open transcanal tunnel starting from the annulus superior to the chorda tympani laterally towards the suprameatal region. Then, through the open tunnel, a bony groove is created in the bone underneath the length of the external auditory canal (EAC) to protect the electrode from extrusion through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…All of the patients in our study group were experiencing this condition because the combination of sensorineural hearing loss and therapy-resistant external otitis is the primary indication for VSB implantation in our clinic. Although no results of studies of VSB surgery on a large group have been published, virtually no conducting wire extrusions have been recorded in large studies on the transcanal or transmeatal approaches in cochlear implant surgery (15,16). In the publications concerning VSB implantation by Truy et al (5) (n = 2) and Bruschini et al (11) (n = 12), no surgical complications were reported.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…All of the patients in our study group were experiencing this condition because the combination of sensorineural hearing loss and therapy-resistant external otitis is the primary indication for VSB implantation in our clinic. Although no results of studies of VSB surgery on a large group have been published, virtually no conducting wire extrusions have been recorded in large studies on the transcanal or transmeatal approaches in cochlear implant surgery (15,16). In the publications concerning VSB implantation by Truy et al (5) (n = 2) and Bruschini et al (11) (n = 12), no surgical complications were reported.…”
Section: Discussionmentioning
confidence: 94%
“…No facial nerve paralysis was reported in the SMA approach, whereas the classic approach led to 2 facial nerve injuries during the posterior tympanotomy. Another transcanal approach in cochlear implantation, called the transmeatal approach, has recently been described by Taibah (15). In this open-tunnel approach, the drilling of a groove that is comparable with that of our approach is combined with the drilling of a parallel tunnel toward the middle ear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In 2009, from the Kingdom of Saudi Arabia (KSA), Taibah 17 described 131 patients who underwent CI by the transcanal approach, with electrodes inserted via Antro-inferior cochleostomy. The group was comprised of 115 children, with ages ranging from 10 months to 14 years, and 16 adults, with ages ranging from 24 to 58 years, with a male-to-female ratio of ∼1:1.…”
Section: The Transcanal (Veria) Approachmentioning
confidence: 99%
“…However, the transcanal approach for cochlear implantation performed in multiple different centers has not been found to be at an increased risk of electrode exposure, infections, or meningitis. There are seven studies in the literature that have described different modifications of the transcanal approach for cochlear implantation on a total of 470 patients, with a range of follow up of 6 months to 7 years . No cases of meningitis or CSF leakage have been reported and there only has been one reported case of electrode extrusion among the 470 patients .…”
Section: Discussionmentioning
confidence: 99%